Evaluating of Improvement Level in Some of Diyala Governorate Departments according to the Eighth Requirement of Standard (ISO10006:2017) - younus faris, Khalid; Jamal Mawlood , Suha (Journal of Economics and Administrative Sciences, 2024)
The research seeks to evaluate the reality of the level of improvement in a number of the Diyala governorate departments and to identify the gap between the actual reality of these departments and one of the requirements of the standard (ISO10006: 2017) through a case study of these departments, which are two departments (Engineering Construction and Buildings) which use tight checklists that are prepared according to the eighth requirement in the specification for improvement. The data are analyzed based on the seven-point Likert scale and statistical equations. The main result of this research at the engineering construction department is that the project management adopted documenting and analyzing the deviations depending on the importance of these deviations, where some minor deviations are dealt with simultaneously without documenting them. The main results at the Department of Buildings are the lack of a sufficient and integrated system for documentation that can be used by the project management, where the department did not specify the system that can be followed in projects and what the procedures for storage, preservation, and distribution, and the department did not develop a mechanism for improvement that can be followed to identify problems and treat them in order not to occur in the future.Paper type: Research paper